Oxepinamide F biosynthesis involves enzymatic d-aminoacyl epimerization, 3H-oxepin formation, and hydroxylation induced double bond migration - Zheng, Liujuan; Wang, Haowen; Fan, Aili; Li, Shu-Ming (Nature communications, 2020)
Oxepinamides are derivatives of anthranilyl-containing tripeptides and share an oxepin ring and a fused pyrimidinone moiety. To the best of our knowledge, no studies have been reported on the elucidation of an oxepinamide biosynthetic pathway and conversion of a quinazolinone to a pyrimidinone-fused 1 H -oxepin framework by a cytochrome P450 enzyme in fungal natural product biosynthesis. Here we report the isolation of oxepinamide F from Aspergillus ustus and identification of its biosynthetic pathway by gene deletion, heterologous expression, feeding experiments, and enzyme assays. The nonribosomal peptide synthase (NRPS) OpaA assembles the quinazolinone core with d -Phe incorporation. The cytochrome P450 enzyme OpaB catalyzes alone the oxepin ring formation. The flavoenzyme OpaC installs subsequently one hydroxyl group at the oxepin ring, accompanied by double bond migration. The epimerase OpaE changes the d -Phe residue back to l -form, which is essential for the final methylation by OpaF. Oxepinamides are a class of fungal oxepins with biological activities. Here, the authors elucidate the biosynthetic pathway of oxepinamide F from Aspergillus ustus and show that it involves enyme-catalysed oxepin ring formation, hydroxylation-induced double bond migration, epimerization and methylation.